2017
DOI: 10.1002/ajim.22688
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long working hours on cerebrovascular and cardiovascular disease; A case‐crossover study

Abstract: An increase in average weekly working hours may trigger the onset of cerebro-cardiovascular disease. Am. J. Ind. Med. 60:753-761, 2017. © 2017. Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…This finding means that workers working long hours have a higher risk of suffering from cardiovascular heart diseases and metabolic syndrome compared to those not working long hours. Some studies have demonstrated that the risk of cardiovascular heart diseases was caused by increase in weekly work hours [102,103]. Yu [104] reported that long working hours, especially 60 or more per week, increased the risk of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This finding means that workers working long hours have a higher risk of suffering from cardiovascular heart diseases and metabolic syndrome compared to those not working long hours. Some studies have demonstrated that the risk of cardiovascular heart diseases was caused by increase in weekly work hours [102,103]. Yu [104] reported that long working hours, especially 60 or more per week, increased the risk of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation in existing studies is the lack of longitudinal assessment of long working hours and psychosocial factors over time, i.e., as time-varying exposures. However, one study from Korea used a case-crossover design and found a significant increase in average weekly working hours right before the cardiovascular event [ 27 ]. Therefore, future studies would benefit from shifting the focus from the assessment of static baseline characteristics to time-varying and triggering effects that may explain the link between long working hours and CVD.…”
Section: Psychosocial Mechanismsmentioning
confidence: 99%
“…Several Korean researchers have studied the relationship between working hours and cerebro‐cardio vascular disease (CCVD), mental illness, and suicide. Some case‐control and case‐crossover studies in Korea have found that long working hours and work intensity could be risk factors of CCVDs . A few studies on the relationship between suicide and overwork using representative national data showed an association between working hours and depressive symptoms or suicide ideation in Korea .…”
Section: Introductionmentioning
confidence: 99%
“…Some case-control and case-crossover studies in Korea have found that long working hours and work intensity could be risk factors of CCVDs. [3][4][5][6] A few studies on the relationship between suicide and overwork using representative national data showed an association between working hours and depressive symptoms or suicide ideation in Korea. [7][8][9] Korea is also one of just a few countries that provide compensation for CCVDs and mental disorders related to long working hours, a heavy workload, or stressful events.…”
mentioning
confidence: 99%